Pengaruh Profitabilitas, Leverage dan Ukuran Perusahaan terhadap Kebijakan Dividen - Achmad Ridhwan; Agustina Ratna Dwiati (Jurnal Akuntansi, Keuangan, dan Manajemen, 2022)
Purpose: This study examines the factors that can affect dividend policy. The factors discussed are profitability, leverage and company size. Therefore, the purpose was to determine whether profitability, leverage and firm size can have an influence on the occurrence of dividend policy. Research Methodology: This research was conducted quantitatively. The population used is the companies engaged in manufacturing and also listed on the Indonesia Stock Exchange for 2016-2018 period. Purposive sampling method was used for determining a sample data. The total data is 149 data. The data testing method uses multiple regression analysis. Results: This research have a result that conclude that profitability have an effect toward dividend policy but leverage and firm size cannot affect dividend policy. Limitations: Generalization of result cannot be used for this research other than manufacturing companies and there are 91% other factors that can affect dividend policy. Contribution: This research contributes in terms of empirical evidence that can be used by investors and/or potential investors to learn about factors that can affect company policy regarding dividens.